The Implementation of Project Based Learning Model Combined with Storyline Learning Technique for German Writing Skill - Muhammad Dilan Humam; Dewi Kartika Ardiyani (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2020)
The purpose of this research is to describe the learning process using project based learning model combined with storyline learning technique and the students’ responses towards the learning model. This research was conducted online through WhatsApp  in the class XI IBB SMAN 6 Malang which consists of 12 students.  This is a descriptive qualitative research using observation and questionnaires as data collection techniques. The research results showed that the implementation of Project Based Learning model combined with Storyline learning technique went well and got  positive responses from the students. Through this learning, students are actively involved in learning activities during the German writing class and it can help students  solving  the existing problems and also can help them expressing their ideas in form of written texts.